PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN TUGAS DAN FUNGSI UPT PARKIR DI PEKANBARU, RIAU - Ulandhary, Maysheila; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The task of the Parking Management Unit (UPT Perparkiran) is to assist the head of the department in carrying out matters in the transportation sector, specifically in the sub-sector of parking management. The UPT Perparkiran has several functions, one of which is to manage the system and procedures for regulating parking in various areas within the city of Pekanbaru. Based on the description above, the purpose of this research is to describe the public's perception of the implementation of the duties and functions of the Parking Management Unit (UPT) in Pekanbaru, Riau. This research was conducted using a descriptive quantitative approach, where the data collection tool used was a questionnaire. The sample in this study is the people of Pekanbaru City who use parking spaces, totaling 60 individuals determined by census technique. The measurement tool used is a questionnaire on public perception of the implementation of the duties and functions of the Parking Technical Implementation Unit in Pekanbaru, Riau, consisting of 15 items. The analysis used in this study is data portrait analysis. Based on the results of the data analysis with descriptive analysis, it was found that the level of public perception regarding the implementation of the duties and functions of the Parking UPT in Pekanbaru, Riau is in the moderate category at 43.4%. The community members who have perceptions regarding the implementation of the duties and functions of the Parking UPT in Pekanbaru, Riau, are mostly aged 20-25 years, with more female respondents compared to male respondents. Keywords: Public Perception, Duties and Functions of the Parking UPT in Pekanbaru, Riau